Preface to Grand Rounds Column - Zeng, Guangqiao; Journal of Thoracic Disease, on behalf of (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
We are delighted to announce the inauguration of a new column at Journal of Thoracic Disease (JTD), the Grand Rounds (GR). The GR is designed to become one of the most featured columns in our journal. Currently, GR articles at JTD replay the sessions where a typically intractable case was discussed among a panel of physicians, radiologists, pathologists, thoracic surgeons, oncologists and other healthcare professionals.